Model Pengembangan Organisasi Dalam Meningkatkan Efektivitas dan Kinerja Lembaga - Rian Nur Hakim (CV. ITTC INDONESIA, 2025)
This article examines various organizational development models that play a strategic role in enhancing the effectiveness and performance of educational institutions. In response to the increasingly dynamic and complex environmental changes, educational institutions are required to be adaptive by implementing well-planned and sustainable organizational development strategies. This study employs a qualitative approach using a literature review method to analyze theories and contemporary practices of organizational development. The findings indicate that several organizational development models, including Lewin’s model, Action Research, Appreciative Inquiry, and Organizational Learning, are effective in promoting performance improvement, innovation, and sustainable institutional effectiveness. The implications of this study highlight the importance of leadership commitment and active participation from all organizational members in supporting the success of organizational change processes.